(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
This paper assessed socioeconomic determinants of crop production strategies adopted by organic farmers in Onicha Local Government Area of Ebonyi State, Nigeria. Specifically, the study analyzed the effects of socioeconomic characteristics of the organic farmers on the type of crop production strategies adopted and determined constraints to organic farming in the study area. Multi-stage random and purposive sampling techniques were used to select the respondents. Primary data collected were analyzed using ordinary least square multiple regression and factor analysis. The null hypothesis was tested at 5% level of significance. Result showed a high value of R2 (87%) which signifies that the socioeconomic characteristics of the respondents had significant effects on the type of crop production strategies they adopted. The independent variables were positively signed and statistically significant at various levels; indicating positive relationship with the dependent variable. Four major constraints identified were: economic/institutional, social, financial and technological constraints. The study recommended that the respondents should be well trained in organic farming and its applications in order to ensure sustainable production of crops in the area.